Bay salt in seventeenth-century meat preservation: how ethnomicrobiology and experimental archaeology help us understand historical tastes. (2022) - Tsai, Grace E.; Anderson, Robin C.; Kotzur, Jackie; Davila, Erika; McQuitty, John; Nelson, Emelie
Abstract: 'Sea salt is made by boiling and evaporating sea water over the fire. Bay salt, by evaporating sea water, in pits clayed on the inside, by the heat of the sun. Basket salt is made by boiling away the water of salt springs over the fire. Rock salt is dug out of the ground', wrote Charlotte Mason in The Lady's Assistant (1775), one of the most comprehensive eighteenth-century cookbooks. Although there were at least four variations of salt before the pre-industrial era, several historical recipes specified the use of bay salt (solar salt) for meat preservation, elevating its cultural status and implying that early modern actors had a refined understanding of salts, their tastes and their applications. This study uses scientific analysis to determine whether there is a biological or chemical basis for the superior reputation of bay salt for curing. Laboratory data suggest that bay salt contains microbes that produce nitrate and nitrite, which give the meat a more favourable taste and pleasant aesthetic. The authors thus demonstrate that combining insights from experimental archaeology with textual analysis of historical sources gives us a deeper understanding of historical uses of taste as an epistemic tool.